Hubungan antara Semangat Kerja dan Gaya Kepemimpinan dengan Motivasi Kerja Perawat di Unit Rawat Inap RSUP Dr. Sitanala Tangerang Tahun 2025 - Dwi Sofiyanti; Dwi Nurmawaty; Intan Silviana Mustikawati; Mayumi Nitami (Pusat riset dan Inovasi Nasional, 2025)
Based on the preliminary study of work motivation measurement, it was found that out of 10 nurses in the inpatient unit of RSUP Dr. Sitanala, 7 of them had low work motivation due to the unfulfilled physiological needs and esteem needs. The objective of this study was to determine the factors associated with nurses’ work motivation in the inpatient unit of RSUP Dr. Sitanala Tangerang in 2025. This study employed a Cross-Sectional design with a total sample of 72 respondents. Data analysis was conducted using univariate and bivariate methods with the Chi-Square test. The results of the univariate analysis showed that most nurses had low work motivation, namely 47 respondents (65.3%), low work enthusiasm (51.4%), and unsupportive leadership style (56.9%). The bivariate analysis revealed that the relationship between work motivation and work enthusiasm showed PR = 0.907 (0.647–1.270), while the relationship between work motivation and leadership style showed PR = 1.613 (1.083–2.402). The conclusion of this study is that work enthusiasm has no significant association with work motivation, while leadership style has a significant relationship with work motivation.